Fiscal Policy and Economic Growth in Nigeria - Onyema, Joseph I.; Onuoha, Ifeanyichukwu (NIU Journal of Social Sciences; Vol 5 No 3 (2019): KIU Journal of Social Sciences, Vol. 5 No. 3, September 2019, 2019)
This study examined the relationship between fiscal policy and economic growth in Nigeria between the periods 1981 to 2017 using time series data. The study employed a disaggregate analysis of various components of government expenditure while taxes and other sources of revenue proxied by government revenue are employed as a measure of fiscal policy. Series of estimation techniques were employed in the process of research and they include unit root test, co-integration test, multiple regression and error correction model. Findings reveal that three of the six proxies of fiscal policy, namely, government expenditure on economic, social services and tax have a positive and significant  relationship with gross domestic product, while government expenditure on administration and fiscal deficit have a negative relationship with economic growth in Nigeria. The study thus concludes that fiscal policy over the years has significantly promoted economic growth in Nigeria. As such, the study recommends that government should adopt fiscal mechanism that will encourage increase in revenue through tax and ensure that more of government spending should be channeled to areas such as economic and social that help to grow the economy given their positive and significant effect on the growth of the economy of Nigeria. Keywords: Fiscal Policy, Government expenditure, Gross Domestic Product